Pengaruh Beban Pajak Tangguhan, Capital Intensity, dan Thin Capitalization terhadap Tax Avoidance - Lia Agustina; Aris Sanulika (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
The aim of this research is to find out how tax avoidance is influenced by deferred tax expense, capital intensity, and thin capitalization in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. In this research, tax avoidance (Y) as the dependent variable, while deferred tax expense (X1), capital intensity (X2), and thin capitalization (X3) as independent factors. The annual financial reports of Consumer Non-Cyclicals Sector Companies listed on the Indonesia Stock Exchange (BEI) for the 2018–2022 period which are available on the official website www.idx.co.id, as well as registered journals or articles, are secondary data sources used in this research . Non-cyclical consumer sector companies listed on the IDX between 2018 and 2022 are the population for this research. By using the EViews version 9 application program, analysis techniques are used. This research concludes that there is a relationship between tax avoidance and deferred tax expense, capital intensity and thin capitalization test findings.